Human Resource Management Practices and Organizational Performance: An Empirical Study of Manufacturing and Service Institutions of Nepal - Pradhan, Gopal Man (The Batuk, 2024)
Modern HRM policies and strategies are replacing traditional personnel concepts in HRM practices, which are continuously changing in Nepalese enterprises. This study is focused on assessing the human resource practices in the manufacturing and service institutions in Nepal and their relationship with organizational performance in terms of employee turnover and productivity. The required data were collected from 12 manufacturing companies and 23 service providing institutions by administering a set of questionnaires. Data were processed on SPSS and EViews. The correlation results suggested that there is negative association between HRM practices and employee turnover whereas there is positive association between HRM practices and productivity. The regression results suggested that there is a negative impact of HRM practices on employee turnover whereas there is positive impact on productivity.